Artistic and cultural training in compulsory secondary education: the cases of France and Mexico - Moreno, Ileana Rojas (Universidad Autónoma de Tamaulipas, 2020)
This article is based on the results of the institutional research project PAPIIT-UNAM IN 401218 on compulsory secondary education in nine countries in Latin America and four in Europe. Here we return to one of its objectives, aimed toward highlighting the similarities and differences in Artistic Education in the curriculum prescribed in two of the countries in the sample (France and Mexico). For this purpose we use a comparative methodological strategy, with the intention of arguing the link between international educational policies and national curricula, in a context characterized by global trends in internationalization, mandatory and standardization of the educational offer. Regarding Artistic Education and its role in achieving a better quality of education, we place its formative contribution in meeting the need of both creativity and cultural awareness in the 21st century.